Pendampingan Pembuatan Hand Sanitizer dan Cairan Disenfektan Homemade dalam Mencegah Covid I9 Di Pondok Pesantren Darul Lughah Wal Karomah” - Qosim, Nanang; Yunus, Moch (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2021)
This online-based mentoring program aims to increase public understanding / knowledge about the many benefits contained in betel leaf. Betel leaf as one of Indonesia's natural wealth, is expected to improve skills through making hand sanitizers from betel and lime leaves online. short video-based counseling that we upload on our YouTube account with a simple method and a relatively affordable cost. Hand sanitizeris a health product that can instantly inhibit and kill germs without using air, can be used anytime and anywhere. This preparation is popular for its easy and practical use where you don't need soap and water. The community / students usually use this product after handling objects, from the toilet or after taking out the trash. There are various types of bacteria that easily stick to human hands such as staphylococcus aureus, E. coli, salmonella and shigella. Food items prepared by direct, unprocessed hand contact are completely contaminated with these bacteria. It is not only our hands that we have to guard because there are objects around us that we also have to protect from germs and how to handle them by spraying homemade disinfectant (homemade) liquid.